A simple and selective UHPLC–MS/MS method for quantification of plantagoguanidinic acid in rat plasma and its application to a pharmacokinetic study. (25th January 2017) - Zhong, Ruijian; Yu, Yan; Zheng, Yangbing; Chen, Weikang; Zhou, Guoping; Ding, Jianhong; Yuan, Mingming
Abstract: A simple, sensitive and specific UHPLC–MS/MS method for quantification of plantagoguanidinic acid (PGA) in rat plasma was applied to investigate the pharmacokinetic behavior in vivo, using protopine as internal standard. The chromatography was separated on a Phenomenex® Luna‐C18 column (2.1 × 150 mm, 3.0 μm) within 7.0 min using a mobile phase consisting of acetonitrile–0.1% formic acid solution under gradient elution at a flow rate of 0.4 mL/min. Prepared samples were monitored by multiple reaction monitoring mode, with the target fragmentions m/z 226.2 → 84.2 for PGA and m/z 354.2 → 188.9 for IS in positive electrospray ionization. The calibration curve of PGA was linear throughout the range 1–1000 ng/mL ( r  = 0.9962). The lower limit of quantitation in plasma for PGA was 0.1 ng/mL, and the recovery was >88.6%. Intra‐ and interday accuracy ranged from −8.6 to 4.9%. Furthermore, this validated method was successfully used for a pre‐clinical pharmacokinetic study of PGA at a single dose of 20 and 5 mg/kg in rats via oral and intravenous administration. The study showed that PGA was absorpted rapidly and eliminated gradually with a greater absolute oral bioavailability of 70.1% in rats.